2019
DOI: 10.1038/s41598-019-41431-7
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and neuronal circuit of spexin 1/2 neurons in the zebrafish CNS

Abstract: Spexin (SPX) is a highly conserved neuropeptide that is widely expressed in mammalian brain and peripheral tissue. In teleost, SPX1 is mainly expressed in the brain and ovary, and is involved in reproduction and food intake. A second form of SPX, SPX2, was recently identified in chick, Xenopus, and zebrafish. The expression pattern and roles of SPX2 are unknown. SPX (spx1) is highly expressed in the vertebrate brain, but its distribution, circuits, and interactions with its putative receptor are unknown. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 46 publications
2
26
0
Order By: Relevance
“…In tilapia, the two spexin paralogs exhibited wide differential tissue distribution patterns, where Spx1a was primarily expressed in the midbrain (containing the hypothalamus in our preparations), and Spx1b was primarily expressed in the anterior brain, which contains the preoptic area. Similarly, in a detailed report of spexin neuron circuitry in zebrafish, Spx1 expression was restricted to the midbrain tegmentum and the hindbrain and Spx2 expression was found in the preoptic area, however neither was detected in the hypothalamus (53). In goldfish, Spx1 was identified in the hypothalamus, thalamus, and medial longitudinal fasciculus, however immunoreactivity was detected using heterologous antibodies that may have recognized both Spx1 and Spx2 (10).…”
Section: Discussionmentioning
confidence: 86%
“…In tilapia, the two spexin paralogs exhibited wide differential tissue distribution patterns, where Spx1a was primarily expressed in the midbrain (containing the hypothalamus in our preparations), and Spx1b was primarily expressed in the anterior brain, which contains the preoptic area. Similarly, in a detailed report of spexin neuron circuitry in zebrafish, Spx1 expression was restricted to the midbrain tegmentum and the hindbrain and Spx2 expression was found in the preoptic area, however neither was detected in the hypothalamus (53). In goldfish, Spx1 was identified in the hypothalamus, thalamus, and medial longitudinal fasciculus, however immunoreactivity was detected using heterologous antibodies that may have recognized both Spx1 and Spx2 (10).…”
Section: Discussionmentioning
confidence: 86%
“…Schematic drawing of the representative localization of SPX1, GALR2a/2b, and GARL3 in the sagittal sections of the brain of various vertebrate species. SPX1 has only localized in rodent (2, 25, 26), goldfish (7), and zebrafish (27, 28). GALR2a/2b was not localized in goldfish.…”
Section: Receptor and Distribution Of Spexins In Vertebratesmentioning
confidence: 99%
“…SPX1 positive cells are also reported in the ventromedial thalamic nucleus and medial longitudinal fasciculus of the goldfish (7), and in the zebrafish (27). Recently, Kim et al (28) reported the detailed distribution of both SPX1 and SPX2 in the brain of the zebrafish. This study is the first to report the localization of SPX2 in non-mammalian vertebrate.…”
Section: Receptor and Distribution Of Spexins In Vertebratesmentioning
confidence: 99%
See 2 more Smart Citations